Microvascular Dysfunction as a Bridge between Chronic Obstructive Pulmonary Disease and Ischemic Events - Amiri, Ali; Rahbani, Roohollah; Abbasnezhad, Mohsen; Maleki, Mehdi; Dadgar, Fatemeh; Jafari , Negar (Galen Medical Journal, 2025)
Chronic obstructive pulmonary disease (COPD), traditionally viewed as a localized pulmonary disorder, is now recognized as a systemic disease with far-reaching vascular consequences. Among its most concerning comorbidities are ischemic events such as myocardial infarction and stroke, which occur at disproportionately high rates in these patients, even after adjusting for shared risk factors like smoking. This unexpected persistence of risk has driven interest in the underlying mechanisms that might link lung dysfunction to vascular pathology. Emerging evidence suggests that microvascular dysfunction (MVD), characterized by endothelial injury, capillary rarefaction, and impaired vasoreactivity, may serve as a pivotal intermediary in this relationship. Systemic inflammation and oxidative stress, initiated in the lungs, appear to spill over into the circulation, damaging the vascular endothelium and setting the stage for atherosclerosis and ischemic injury. This review synthesizes current findings from molecular, imaging, and epidemiological studies to propose MVD as a central mechanistic bridge between COPD and ischemic events. We also examine therapeutic strategies that target endothelial health and highlight potential opportunities for early intervention. By reframing COPD as a disease with significant vascular implications, this review underscores the need for an integrated clinical approach that goes beyond pulmonary function and addresses systemic vascular health.